Teaching friction at university level through an experiment with images - Leite, Marcos L. (2021)
The experiment with images described here contributes to the scarce literature about the experimental approach to the classical problem of oblique launching on the surface of an inclined plane. It is directed at an intermediate physics course, with the aim of contextualizing the teaching of the laws of friction and empirical modeling in Classical Mechanics. We used a video of a two-dimensional real motion of a coin sliding on an inclined plane, a case where the net force varies continuously. The video frames were separated and each one was assigned a time code by a computational process. The resulting set of images was used to analyze the dynamical evolution of the system, by recording the coin positions at known instants. All the images and laboratory manuals can be accessed at http://www.fep.if.usp.br/∼fisfoto/translacao/planoInclinado/index.php. Realizing that the resistive force can be interpreted as the kinetic friction force, according to Amontons’ laws, it is possible to build a theoretical model able to predict the trajectory through a first order numerical method, and then fit its parameters to the observed trajectory. This proposal reconciles the laboratory with Information and Communication Digital Technologies (ICDT). It also favors a deeper discussion about the role of laws, models and hypotheses in the physical sciences, which could be particularly interesting in the case of teacher education.